Diabetes-Related-Distress and its Relationship with Glycaemic Control Among Type 2 Diabetes Mellitus Patients Attending a Specialty Clinic in Lagos, Nigeria - Omotosho A; Sodipo OO; Malomo SO; Dada AO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Background: Diabetes Mellitus (DM) is a chronic metabolic disease with various complications throughout its course. The presence of emotional burden in diabetes disease, which is referred to as diabetes-related distress (DRD) is common among such patients and may affect their response to treatment. Objectives: To assess the relationship of diabetes-related distress and glycaemic control among patients with Type 2 Diabetes mellitus. Methods: This hospital-based cross-sectional study was conducted at the Family Medicine Department of LASUTH, Ikeja, Lagos. A total of 317 patients with Type 2 Diabetes mellitus were systematically recruited. The data were collected over a four-month period. Important clinical information including clinical characteristics and diabetes-related distress using the diabetes distress scale (DDS-17) was collected. Glycosylated haemoglobin (HbA1c) was also assessed. Results: The degrees of DRD were as follows: 54.9% (None/little), 40.1% (moderate) and 5.0% (severe). The mean HbA1c estimate for all participants was 7.83±1.8%. Among the 317 study participants, 67.2% had poor glycaemic control while 32.8% had good glycaemic control. There was a statistically significant association between DRD and glycaemic control (p< 0.001). Likewise, the various domains of DRD had statistically significant associations with glycaemic control with the exception of physician-related domain. Participants with better glycaemic control reported lower levels of DRD than participants with poorer glycaemic control. Conclusion: There is a high level of diabetes-related distress patients with diabetes mellitus. Good glycaemic control is important in improving or preventing DRD. Therefore, T2DM patients should be screened for DRD during their treatment.